PROSPEK PENGEMBANGAN OBJEK WISATA BULUH CINA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Khairunnisa '; Tri Sukirno Putro; Lapeti Sari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to determine: (1) the potential of what is contained in Attractions Buluh China; (2) what efforts conducted by local government in developing Attractions Buluh China; and (3) whether the constraints faced by operators in the development of attractions Buluh China. This research is located in the village Buluh China Subdistrict Siak, Kampar. The data in this study were obtained by interviewing, observation, and kuesinoer. Then the data analysis in this research using SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). Based on the SWOT analysis through a combination of internal and external factors that can formulate alternative strategies for tourism development Buluh China is by utilizing the power (strength) and opportunities (opportynity), namely: (a) optimize the development of attractions Buluh China through optimization of promotional activities involving public and private parties; (B) take over management of natural resources can be used as a tourist attraction (the condition of unspoiled nature, biodiversity, seven natural lakes) through cooperation undertaken by local governments and private parties; (C) promotion optimally through the management improvements made so that visitors are more interested to come visit attractionsKeywords: Development, Prospects, Tourist Attraction Buluh China